Feline morbillivirus in northwestern Italy: first detection of genotype 1-B. Issue 6 (June 2021) - Muratore, Elvira; Cerutti, Francesco; Colombino, Elena; Biasibetti, Elena; Caruso, Claudio; Brovida, Claudio; Cavana, Paola; Poncino, Laura; Caputo, Maria Pia; Peletto, Simone; Masoero, Loretta; Capucchio, Maria Teresa
Objectives: A novel morbillivirus was recently described in stray and domestic cats in Asia, the USA and Europe. Most cats infected with feline morbillivirus (FeMV) showed lower urinary tract or kidney disease. Although the association of FeMV infection and kidney diseases has been suggested, the virus pathogenicity remains unclear. The present study aimed to investigate the distribution of FeMV infection, as well as the relationship between FeMV infection and kidney diseases in cats from northwestern Italy. Methods: A total of 153 urine samples (150 individuals and three pools) and 50 kidney samples were collected and included in the study; total RNA was extracted and a reverse transcription quantitative PCR (RT-qPCR) was performed in order to identify FeMV. Kidneys were also submitted to anatomopathological examination. Phylogenetic analysis and isolation attempts were carried out on positive samples. In FeMV-positive cats, urinalysis and blood analysis were performed. Results: FeMV RNA was detected in 7.3% of urine samples and in 8% of kidney samples, both in healthy cats and in cats with clinical signs/post-mortem lesions compatible with kidney disease. At histopathological examination, tubulointerstitial nephritis (TIN) was shown in 3/4 positive kidney samples, but a clear relationship between FeMV and TIN was not observed. Isolation attempts were unsuccessful, although the urine sample of one castrated male cat hosted in a cattery showed a positive signal in RT-qPCR until the fourth cell passage. Phylogenetic analysis revealed that this FeMV strain belonged to genotype 1-B. In the same cattery, a second genotype 1-B variant was detected from a urine pool. Urinalysis showed proteinuria in three cats, while at blood analysis three cats presented altered creatinine levels. Conclusions and relevance: Data reported suggest the presence of a FeMV sub-cluster distinct from the strain previously isolated in Italy, whose role in renal disorders remains uncertain.